2020
DOI: 10.3390/jcm9030853
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Temporal Relationship between Cancers and Systemic Sclerosis: A Clinical Series from Montpellier University Hospital and Review of the Literature

Abstract: Cancer among patients with systemic sclerosis (SSc) would appear to be more prevalent than in the general population. Pathophysiological hypotheses are multiple, involving intertwined factors such as immune system antitumoral response, oxygen species dysregulation, and immunosuppressive treatments. We aimed to identify SSc patients with cancer monitored at our center, describing their clinical and immunological characteristics, such as cancer-specific outcomes. We focused in particular on the temporal relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
11
0
2
Order By: Relevance
“…Moreover, haematological complications were demonstrated to be more common in older age in diffuse cutaneous systemic sclerosis, and lymphoma was diagnosed within the first years of systemic sclerosis. Gastrointestinal lymphomas constituted a substantial percentage of all the lymphomas diagnosed [27,28].…”
Section: Association Of Systemic Sclerosis With Myeloproliferative Anmentioning
confidence: 99%
“…Moreover, haematological complications were demonstrated to be more common in older age in diffuse cutaneous systemic sclerosis, and lymphoma was diagnosed within the first years of systemic sclerosis. Gastrointestinal lymphomas constituted a substantial percentage of all the lymphomas diagnosed [27,28].…”
Section: Association Of Systemic Sclerosis With Myeloproliferative Anmentioning
confidence: 99%
“…Previous studies have shown a 1.5-fold increase in cancer risk in SSc patients compared with the general population, especially lung cancer, hematological malignancies, and breast cancer (BC) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Many theories have been put forward to explain this association: firstly, exposure to immunosuppressive therapies; secondly, genetic susceptibility to both malignancy and the development of autoimmune disease; and finally, a common inciting exposure or more likely a multifactorial pathogenic mechanism involving both genetic contributions as well as other cancer risk factors [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Colaci et al observed a significant increase in BC incidence compared with the general population from the same geographic area with a close temporal relationship between SSc and BC onset [ 6 ]. This close temporal relationship suggests that early onset of BC might trigger the immune system, leading to an excessive immune response and the onset of SSc [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, existen numerosos estudios que muestran una asociación entre la presencia de cáncer o determinados tipos de cáncer y patrones de autoanticuerpos pero resulta difícil establecer una asociación clara por el escaso número de trabajos para cada anticuerpo y las dificultades metodológicas asociadas. Así, los anticuerpos anti-ARNp III han sido descritos de forma consistente como predictores de riesgo de desarrollo de cáncer, y como su presencia indicativa de una estrecha asociación temporal entre el diagnóstico de malignidad y el inicio clínico de la ES, teniendo estos pacientes mayor riesgo de desarrollar cáncer durante los primeros dos años tras el inicio de la ES (76,(86)(87)(88)(89)(90)(91) Por otro lado, no solo la presencia de anticuerpos se ha relacionado con cáncer; pacientes con anticuerpos antinucleares (ANA) positivo, pero ausencia de ACA, ATA o ARNp III (la ausencia de estos autoanticuerpos son los denominados pacientes "triple negativo") también se han relacionado con incremento del riesgo de cáncer por algunos autores, lo que sugiere que puede haber otros subconjuntos serológicos aun desconocidos de esclerodermia asociada al cáncer (77,86,92,100).…”
Section: Cáncer Y Anticuerposunclassified
“…Al revisar la literatura, encontramos que en la mayoría de los trabajos publicados antes del año 2014 el cáncer de pulmón se identificaba como la neoplasia más frecuente, mientras que el cáncer de mama solía ocupar la segunda posición (23,94,141,142,144,151,152,154). Por el contrario, en los estudios más recientes esta relación se invierte, coincidiendo con nuestros resultados (77,95,100,126,149,150). Una posible explicación puede ser el aumento de la detección de la neoplasia de mama facilitado por los cribados establecidos para esta neoplasia en la última década.…”
Section: Localizaciones Tumorales Más Prevalentes En Esclerosis Sistémicaunclassified